Nature Club Activity: Knowledge Exploration on Javan Slow Loris (Nycticebus javanicus) and Protected Endemic Animals in Conservation Education Program - Muthmainnah, Rifaatul; Mulyani, Leni Sri; Fitriyani, Wina (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2023)
Conservation education can increase knowledge about endangered animals, one of which is the Javan slow loris (Nycticebus javanicus), and protected endemic animals in Indonesia, and this can be done through the nature club activity as one of the conservation education programs. However, most students are indifferent to conservation or science education. This individual influence is the characteristics and dispositions students bring to learning, such as interest, effort, values, and perceived abilities. This study aims to determine the effectiveness of conservation education programs through nature club activities on students' knowledge of Javan slow loris and protected endemic animals. The research method is the experimental method, with the research design used as one group pretest-postest design; the data collection technique is done by test and observation. The results showed that the activities carried out were effective on students' knowledge of Javan lorises and protected endemic animals, as evidenced by the calculation of the N-gain score indicating that the average N-gain score (mean) was 0.614.ABSTRAK: Pendidikan konservasi dapat menambah ilmu mengenai hewan yang terancam punah salah satunya yaitu Kukang Jawa (Nycticebus javanicus) serta hewan endemik yang dilindungi yang ada di Indonesia, hal ini dapat dilakukan melalui program klub alam yang ada pada pendidikan konservasi. Akan tetapi mayoritas siswa belum mendapatkan pendidikan konservasi dan hanya menjadi bagian kecil dari pendidikan sains. Penelitian ini bertujuan untuk mengetahui efektivitas pendidikan konservasi melalui kegiatan klub alam terhadap pengetahuan siswa mengenai kukang jawa dan hewan endemik yang dilindungi. Metode penelitian yang digunakan yaitu metode eksperimen, dengan desain penelitian yang digunakan adalah one group pretest-posttest design, teknik pengumpulan data dilakukan dengan tes dan observasi. Hasil penelitian menunjukkan bahwa kegiatan yang dilakukan efektif terhadap pengetahuan siswa mengenai kukang jawa dan hewan endemik yang dilindungi, dibuktikan dari hasil perhitungan N-gain score menunjukkan bahwa rata-rata skor N-gain (mean) adalah 0,614